Collaborative neural processes predict successful cognitive‐motor performance. (24th November 2022) - Chueh, Ting‐Yu; Lu, Calvin M.; Huang, Chung‐Ju; Hatfield, Bradley D.; Hung, Tsung‐Min
Abstract : Psychomotor efficiency is achieved by expert performers who exhibit refined attentional strategies and efficient motor program execution. Further understanding of the psychomotor efficiency hypothesis requires examination of the co‐activation of key electroencephalographic (EEG) indices, including frontal theta (Fθ) power, left temporal alpha (T3α) power, the sensory‐motor rhythm (SMR), and frontocentral alpha power (FCα). This study examined the relationship between these selected neural processes and the odds of successful cognitive‐motor performance. EEG indices of successful and failed putts observed in twenty‐seven skilled golfers were subjected to mixed‐effects logistic regression analysis. The results revealed that concurrent elevations of Fθ and T3α were associated with increased odds of successful performance. The co‐activation from motoric processes indicated by SMR and FCα also elevated the odds. Overall, the findings emphasize that refined attention allocation and effective motor program processing are essential cognitive features of superior cognitive‐motor performance for skilled golfers.